A Preference-Based Supervising of Virtual Machines in Cloud Environment - Ezhilarasi, B; Padmakumari, P; Umamakeswari, A (International Journal of Engineering and Technology, 2018)
Cloud Computing is a well-known technology in todayâ€™s world. A large number of users are benefited from the cloud services. The cloud computing must provide efficient service on time for customer satisfaction. So, prominent resource monitoring and scheduling techniques are needed. To achieve the customer satisfaction and to reduce the communication overhead, a method called Resource Supervisor (RS) is proposed. The proposed algorithm assigns the preference for the tasks having highest length, monitor the status of the resource and schedule the tasks to various resources quickly. The proposed method is implemented using Cloud Simulator, and experimental results are validated by comparing RS method with existing algorithms, which provides better outcomes and reduces the communication overhead.Â